Pengaruh Opini Audit Ukuran Kap Dan Profitabilitas Terhadap Auditor Switching Dengan Financial Distress Sebagai Variabel Moderasi - Arbaini Dwi Saputri; Hansen Rusliani; Efni Anita (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to determine how the effect of audit opinion, KAP size and profitability on auditor switching with financial distress as a moderating variable. This research was conducted on companies registered on the Jakarta Islamic Index (JII) for 2019-2021. The theory used in this research is agency theory. The method of determining the sample using purposive sampling which consists of 11 companies. This study used a quantitative method with data analysis methods, namely using logistic regression which was processed with the SPSS Ver. application. 26. The results of this study indicate that audit opinion has a significant negative effect on auditor switching. KAP size and profitability has no effect on auditor switching. Financial distress is not able to moderate the effect of audit opinion, KAP size and profitability on auditor switching in companies listed on the Jakarta Islamic Index (JII) in 2019-2021.